Influence of mandibular setback surgery on three-dimensional pharyngeal airway changes. Issue 8 (August 2019) - Lee, S.-T.; Park, J.-H.; Kwon, T.-G.
Abstract: The aim of this study was to investigate the factors influencing three-dimensional changes in pharyngeal airway space after mandibular setback surgery. Airway changes in 48 skeletal class III patients who had undergone mandibular setback surgery alone ( n = 25, group 1) or with maxillary surgery ( n = 23, group 2) were analyzed. Linear parameters, cross-sectional area, and volumes of the pharyngeal airway were evaluated before (T0), immediately after (T1), and 1 year after surgery (T2) by cone beam computed tomography. Although the reduced airway volume and cross-sectional area recovered slightly in the long term after surgery, the total pharyngeal airway volume (TPV) was significantly reduced compared to baseline, by 15% in group 1 and 12% in group 2. Regression analysis showed that maxillary posterior impaction in two-jaw surgery had a protective effect on preserving TPV. A change in body mass index from T0 to T2 was an important predictor of decreased TPV in one-jaw surgery patients. Maxillary posterior impaction can be a reliable option for compensating the pharyngeal airway reduction after mandibular setback surgery. Postoperative weight gain can increase the risk of postoperative pharyngeal airway reduction. Therefore, these factors need to be considered before and after mandibular setback surgery.